Rey meets BB-8 - Schaefer, Elizabeth (Adaptor); Rood, Brian (Los Angeles : Disney/Lucasfilm Press, 2015)
Scavenger Rey lives a lonely existence on the planet Jakku until a visit by droid BB-8 changes her life forever.
At head of title: Star Wars : The Force Awakens.
Keywords: Robots -- Fiction; Extraterrestrial beings -- Fiction; Space warfare -- Fiction; Adventure and adventurers -- Fiction; Robots -- Fiction; Extraterrestrial beings -- Fiction; Space warfare -- Fiction; Movie novels; Adventure fiction; Science fiction